2005
DOI: 10.1021/bi050272k
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relation of Human β-Defensin 3:  Influence of Disulfide Bonds and Cysteine Substitution on Antimicrobial Activity and Cytotoxicity

Abstract: Human beta-defensins form a group of cysteine-rich antimicrobial peptides which have been found in epithelial tissue and, more recently, in the male genital tract. They play a role in the defense against microbial pathogens in innate immunity and display additional chemotactic functions in the adaptive immune system. An important characteristic of antimicrobial peptides is that they also exhibit toxic potential on eukaryotic cells. Very little is known about the structure dependence of antimicrobial and cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
181
3
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(206 citation statements)
references
References 61 publications
13
181
3
7
Order By: Relevance
“…This could imply that disulfide bonding is essential to the functional structure of the molecules. However, in the case of HBD-3, disulfide bonding was relevant only for its chemotactic but not its antimicrobial activities [17,33]. In keeping with these studies, we observed that a linear form of HBD-3 had lost its ability to chemoattract macrophages.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This could imply that disulfide bonding is essential to the functional structure of the molecules. However, in the case of HBD-3, disulfide bonding was relevant only for its chemotactic but not its antimicrobial activities [17,33]. In keeping with these studies, we observed that a linear form of HBD-3 had lost its ability to chemoattract macrophages.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, a linear form of HBD-3 was synthesized by alkylation of reduced HBD-3 with iodoacetamide [33]. In this peptide, all cysteine residues are present as S-carboxamidomethylcysteine to suppress the reactivity of the thiol groups.…”
Section: Reagentsmentioning
confidence: 99%
“…The most significant determinant of the anti-E. coli activity of hBD1 mutants is the net charge. The importance of basic residues for antimicrobial activity of defensins has been reported previously for bovine ␤-defensin 2 and 12 (48,51) and hBD3 (46,47). A distribution of the residues important for anti-E. coli properties of hBD1 over the molecule (surface) is illustrated in Fig.…”
Section: Discussionsupporting
confidence: 55%
“…The charged residues are not the only ones to play a role in the antimicrobial properties of defensins (43,47,54,55). In our anti-E. coli assays, mutants Y03A, N04A, V06A, S08A, and L13A are either inactive or very poorly active.…”
Section: Discussionmentioning
confidence: 77%
“…Clearly, native ␣-defensin structure, while dispensable in the killing of E. coli, is required for efficient killing of S. aureus, reminiscent of D HNP1 and D HD5. Due to an unusually high number of cationic charges, the bactericidal activity of HBD3 is generally insensitive to loss of or topological change in disulfide bonding (44,62,63). To extend our previous observation (44), we quantified dose-dependent killing of E. coli and S. aureus by HBD3, .…”
Section: Enantiomeric Human Defensinsmentioning
confidence: 96%